2018
DOI: 10.2142/biophysico.15.0_204
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of crude viper venom action by silver nanoparticles: A biophysical and biochemical study

Abstract: This investigation understands the interaction between lyophilized crude Viper snake venom (Doboia russellie) and Silver nanoparticles (SNPs) using biophysical and biochemical approaches. SNPs were synthesized by chemical reduction method and characterized using UV-Visible spectroscopy, Dynamic Light Scattering (DLS) and Transmission electron microscope (TEM). The average hydrodynamic size of SNPs was found to be 52 nm with 0.261 PDI. TEM image revealed the spherical shape of SNP. Interaction of SNPs and viper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…In this context, Gomes et al conjugated gold nps with the antivenomous compound 2-hydroxy-4-methoxy-benzoic acid (HMBA) extracted from the herb Anantamul ( H. indicus ), which was found to be effective in neutralizing all kinds of toxicity generated by the venom of the deadly Russell’s viper [ 118 ]. Likewise, silver nps were used to inhibit snake venom toxicity completely [ 119 ]. Recently, Chakrabartty et al found that TiO 2 nps are able to neutralize the venom-induced lethal activity of Daboia russelii and Naja kaouthia .…”
Section: Reviewmentioning
confidence: 99%
“…In this context, Gomes et al conjugated gold nps with the antivenomous compound 2-hydroxy-4-methoxy-benzoic acid (HMBA) extracted from the herb Anantamul ( H. indicus ), which was found to be effective in neutralizing all kinds of toxicity generated by the venom of the deadly Russell’s viper [ 118 ]. Likewise, silver nps were used to inhibit snake venom toxicity completely [ 119 ]. Recently, Chakrabartty et al found that TiO 2 nps are able to neutralize the venom-induced lethal activity of Daboia russelii and Naja kaouthia .…”
Section: Reviewmentioning
confidence: 99%
“…2,3 This meets with the global strategy of the World Health Organization for the prevention and control of snakebite envenoming. 4,5 Considering that serum therapy is efficient for systemic but not for local effects and that it must be administered early after envenomation to increase the odds of a successful treatment, which is an unfavourable condition to inhabitants of rural areas from many countries, the nanoparticles come as a promising option against snakebites 6 and have already shown their value with the venoms of Naja nigricollis (Elapidae), 2 Doboia russellie (Viperidae), 7 Bothrops jararaca and Bothrops erythromelas (Viperidae), 8 Bothrops jararacussu (Viperidae), 9 Daboia russelii (Viperidae) and Naja kaouthia (Elapidae). 10,11 The reasons for use of the nanoparticles include the venom toxins bridging as the interface for drug delivery and targeted therapy, 6 as shown with the antigen delivery of encapsulated Naja naja oxiana venom in chitosan nanoparticles targeting tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…8 Nanoparticles have also been used for more specific objectives. The silver nanoparticles promote protection against the neuromuscular blockade induced by Bothrops jararacussu venom 9 and the proteolytic effects of Doboia russellie venom, 7 while abiotic hydrogel nanoparticle mitigates the progression of local tissue damage induced by a diverse array of phospholipases A 2 and 3FTX isoforms found in Naja nigricollis venom. 2 The Colubridae snakes Philodryas olfersii (P. olfersii) and Philodryas patagoniensis (popularly known as green snakes) are opisthoglyphous, considered as not poisonous, 13 and restricted to South America.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations